Effects of different dietary lipid sources (perilla, fish, and soybean oils) on growth, lipid metabolism, antioxidant, and immune status in Chinese giant salamander (Andrias davidianus) - Guo, Yi-Hua; Ma, Jun-Kang; Xu, Hang-zhong; Li, Wei-long; Liu, Chang-Jiang; Lu, Hua; Li, Hong; Zhai, Xu-liang; Xue, Yang; Luo, Li (Frontiers in Marine Science, 2023)
Introduction Perilla oil is a natural vegetable oil rich in alpha-linolenic acid extracted from Perilla seeds. Fish oil is a commonly used animal fat containing a large amount of n-3 polyunsaturated fatty acids. Soybean oil is a commonly used vegetable oil rich in linoleic acid. This study aimed to determine whether perilla, fish, or soybean oil can be used as a lipid source in the diet of the Chinese giant salamander (Andrias davidianus). Methods Three isonitrogenous and isolipidic diets were created by adding 3.0% each of soybean oil (SO), fish oil (FO), and perilla seed oil (PSO). Eight adolescent giant salamanders were fed in rectangular tanks for 98 days with a total of 96 giant salamanders (mean body weight = 75.20g) and were fed an experimental diet until satiation. Results and Discussion The viscerosomatic index and crude lipid content of muscle were found to be considerably lower and the muscle crude protein was substantially higher in the PSO group than in the other groups (P<0.05). Linoleic acid levels were highest in SO, eicosapentaenoic acid and docosahexaenoic acid levels were highest in FO, and α-linolenic acid levels were highest in PSO in A. davidianus muscle tissue (P<0.05). The results of study indicate that the PSO diet can significantly increase the total antioxidative capabilities in the liver and intestine, by elevating the activities of total superoxide dismutase, carnitine transferase-1, and acetyl-CoA carboxylase in the liver. Meanwhile, the immunoglobulin M and high-density lipoprotein cholesterol levels were higher in the blood (P<0.05). Furthermore, it significantly reduced hepatic malondialdehyde, plasma endotoxin, D-lactic acid, and total cholesterol levels, and plasma alkaline phosphatase, diamine oxidase, aspartate transaminase, and alanine transaminase activities (P<0.05). Therefore, perilla, fish, and soybean oils can be used as single lipid sources for A. davidianus with respect to growth performance. On the other hand, perilla oil can enhance crude protein content of muscle, increase Immunoglobulin M(IgM) content and Alkaline phosphatase(AKP) enzyme activity, promote lipid metabolism, and maintain the health of the liver and intestine in A. davidianus.